Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Simplify 6/x-1 - 5x/4

Sagot :

6/(x-1) - 5x/4 = 24/4(x-1) - 5x(x-1)/4(x-1) = (24-5x(x-1))/ 4(x-1) = (19-5x^2-5x)/4x-4 = (5x^2 +5x - 24)/ 4x-3

Answer:  (5x^2 +5x - 24) / (4x-4)

Even though it doesn't look simpler... lol